Impulsive second‐order sliding mode control in reduced information environment. (5th February 2018) - Aldukali, Fathi M.; Shtessel, Yuri B.; Plestan, Franck
Summary: The perturbed system with input‐output dynamics of arbitrary and well‐defined relative degree is considered in a reduced information environment. A novel impulsive second‐order sliding mode control in the reduced information environment is proposed. The almost instantaneous convergence to the origin is achieved via impulsive control acting in a concert with second‐order sliding mode control, specifically supertwisting and twisting algorithms. The impulsive actions are implemented in a piecewise constant format. Numerical examples illustrate the efficiency of the proposed control algorithms.